2002
DOI: 10.1029/2001ja007553
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between multiple substorm onsets and the IMF: A case study

Abstract: The relationship between a series of Pi2 pulsations and their associated substorm onsets with the IMF is examined on 5 May 1999. The magnetograms from the CANOPUS array show the occurrence of three substorm onsets, accompanied by Pi2 bursts. Analysis of the auroral electrojet location and current intensity as deduced from the Churchill line in the CANOPUS array shows that the following onsets move poleward. ACE and Wind magnetic field data show that the first onset occurs during a period of weak southward inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…In other words, GOES 8 was orbiting from the dawn sector to the morning sector and GOES 10 was going into the dawn sector from the postmidnight sector. The magnetic field at GOES 8 and GOES 10 satellites is defined as: H p, perpendicular to the satellite orbital plane (or paral- These results are similar to those studied by Cheng et al (2002b) and confirm the formation of the substorm current wedge after onsets of two Pi2 bursts. Although GOES 8 was at the dawn sector during the time of interest, the effect of the substorm current wedge could continue from the nightside to the dayside hemisphere.…”
Section: October 8 1999supporting
confidence: 74%
“…In other words, GOES 8 was orbiting from the dawn sector to the morning sector and GOES 10 was going into the dawn sector from the postmidnight sector. The magnetic field at GOES 8 and GOES 10 satellites is defined as: H p, perpendicular to the satellite orbital plane (or paral- These results are similar to those studied by Cheng et al (2002b) and confirm the formation of the substorm current wedge after onsets of two Pi2 bursts. Although GOES 8 was at the dawn sector during the time of interest, the effect of the substorm current wedge could continue from the nightside to the dayside hemisphere.…”
Section: October 8 1999supporting
confidence: 74%
“…This indicates that this substorm onset can occur when the IMF becomes strongly northward with a declining B y component. As studied by Cheng et al [2002b], the substorm onset occurs while the magnitude of IMF B y decreases. As a result, the reason why sometimes more than two consecutive Pi2 bursts occur may be attributed to the southward IMF moving back to north again and accompanied by a decreasing B y component.…”
Section: Discussionmentioning
confidence: 97%
“…Following Lyons et al [1997], Blanchard et al [2000] attempted to establish the predictability of substorm onsets followed by sharp northward turnings of the IMF and found that some prediction failures may result from an increase in the B y magnitude which presumably opposes magnetotail convection. In addition, Figure 6b in the work of Cheng et al [2002b] shows that the B y magnitude of the IMF decreases before the third onset. Thus the question arises when the IMF becomes northward, can an increase in the B y magnitude stop substorm onset, and can a decrease in the B y magnitude restart onset?…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations